F-Waves – Physiology and Clinical Uses - Morris A. Fisher (The Scientific World Journal)
F-waves are low amplitude responses produced by antidromic activation of motoneurons. They may not appear after each stimulus and are inherently variable in latency, amplitude, and configuration. Meaningful analysis of F-waves requires an appreciation of these characteristics of F-waves as well as an understanding of their physiology. These features of F-waves as well as their physiology are reviewed. This is important since F-waves are one of the most frequently used studies in clinical neurophysiology and much of the controversies surrounding the use of F-waves relates to a failure to adequately consider the requirements of F-wave analysis. These requirements include the number of F-waves that need to be recorded, the parameters that should be evaluated, and the muscle from which the F-waves are recorded. If analyzed correctly, current reports would indicate that F-waves are the most sensitive and reliable nerve conduction study for evaluating polyneuropathies, can be abnormal in focal proximal nerve dysfunction, can be at least as sensitive as needle electromyography for defining lumbosacral radiculopathies, and can provide a meaningful physiological window into disorders of the central nervous system. Reports supporting these statements and their clinical relevance are discussed.